Singapore Lectures 1980-2018 A Selection - Aung San, Suu Kyi; Cook, Malcolm; George H.W., Bush; Helmut, Schmidt; Henry, Kissinger; Junichiro, Koizumi; Kim, Dae-jung; Kofi A., Annan; Mahathir, Bin Mohamad; Mark, Rutte; Milton, Friedman; Narendra, Modi; et al. (ISEAS Publishing, 2021)
Over the last 40 years, the ISEAS - Yusof Ishak Institute has been honoured to partner with the Singapore government in hosting 44 Singapore Lectures. The Singapore Lecture series is a unique public platform for world leaders and experts visiting Singapore that reflects the city-state's role as a global hub of ideas and diplomacy. The 21 lectures chosen for this 40th anniversary volume chart the fundamental changes in the global economy and the inter-state system that Southeast Asia and Singapore have successfully navigated over these four momentous decades. "The Singapore Lectures reflect the city-state's progress for the past forty years. This selection skilfully captures the highlights from the way Singapore began to learn to read the world to how it became an open and inclusive site of globalization. The collection might do more. The leaders from the five continents who spoke at ISEAS had come to share their experiences, their wisdom and, not least, their dreams. Following what they offered gives us a multifaceted picture that is instructive. It gives readers the chance to review an era of intense rivalry during which political conflicts were accompanied by unprecedented economic growth, when lessons were learnt from tragic failures and leaping successes. Read together, the lectures give us hope in a time of unprecedented global turmoil: there will surely be future leaders who could find ways to rid the world of its demons."--Wang Gungwu, Professor, National University of Singapore (NUS), and former Chairman of the ISEAS - Yusof Ishak Institute Board of Trustees